VREDEN RUSSIAN RESEARCH INSTITUTE OF TRAUMATOLOGY AND ORTHOPEDICS - K. A. Vorobyоv; S. A. Bozhkova; R. M. Tikhilov; A. Zh. Cherny (Travmatologiâ i Ortopediâ Rossii, 2017)
Currently, the use of bone allografts for reconstructive orthopedic surgery in clinical practice around the world is becoming a common procedure. Bone allografts are the first substitute material to the autologous bone and the best alternative to any artificial substituting material. The methods used for the preservation, processing and sterilization of bone are changing and evolving with time. The main goals remain the same including exclusion of infections and creation of the material with sustained properties of the normal bone.The present review reflects the essential methods for biological tissue processing, sterilization and preservation with the analysis of the key requirements for manufacturing of safe allogeneic osteoplastic materials with osteoinductive, osteoconductive and osteogenic properties.